Case report: Giant unilocular prostate cystadenoma: A rarer condition with a single cystic mass - Wang, Wenda; Xiao, Yu; Fang, Shiyuan; Qiao, Yi; Rong, Shi; Wang, Fengdan; Sun, Hao; Jin, Zhengyu (Frontiers in Oncology, 2022)
Prostate cystadenoma is a rare benign prostatic neoplasm which grows outside prostate and locates midline between the urinary bladder and rectum. It usually presents as multilocular cysts, thus named giant multilocular prostate cystadenoma. The definite diagnosis is difficult to be made before surgery and it depends on histopathology. Here we report a rarer condition of prostate cystadenoma which manifests as a giant unilocular cyst with a solid nodule inside. The 55-year-old Chinese male patient presented with dysuria and constipation. MRI revealed a 10.5 × 8.2 cm mono-cystic lesion displacing the rectum to the posterior, prostate and bladder to the anterior, with a 2.8 × 2.1 cm solid nodule at the anterior wall. 18F-FDG PET/CT demonstrated an elevated SUVmax (3.5) of the solid nodule. Laparoscopic pelvic mass resection was performed and prostate cystadenoma was diagnosed. In conclusion, when a mass of single locular cyst sits in the male pelvis, the diagnosis of prostate cystadenoma could not be excluded.